ПР ОФЕ СІЙ НА ПІ ДГОТОВКА ПЕ ДАГОГІ В: ДОСВІД МІ ЖДИСЦИПЛІ НАРНОГО ДОСЛІ ДЖЕННЯ - Sergeyenkova, O (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted the analysis of essence and maintenance of professional preparation of teachers. The necessity of reformation of the system of educational is reflected coming from positions personality, individual approaches